Implementasi Kurikulum Merdeka di PAUD Nurul Ikhlas Kemantan Kebalai Kabupaten Kerinci - Regil Sriandila; Dadan Suryana; Nenny Mahyuddin (Journal on Education, 2023)
This study aims to analyze the implementation of the independent curriculum for PAUD Nurul Ikhlas in Kemantan Kebalai, Kerinci, Indonesia. The independent curriculum has changed the paradigm in implementing education at PAUD Nurul Ikhlas. Even though the number of students is 40 people with 5 teachers and 1 educator, PAUD Nurul Ikhlas is a very important PAUD in Kemantan Kebalai in an effort to provide facilities for healthy and optimal child growth and development in accordance with community values, norms & expectations. Research using descriptive quantitative research methods. Data collection was carried out by questionnaire, literature study, observation, and the documentary method. The instruments that researchers use are as follows. Questionnaire and Documentation Guidelines. The results of the study show that Nurul Ikhlas PAUD Education in implementing the independent curriculum is carried out by providing maximum and rich experience and stimulation. So it is necessary to have a conducive environment for the growth and development of children in Kemantan Kebalai. The method and approach used is an independent learning-based approach, including play-learning.